Ocurrencial culture. Movida pop, modernity and time of changes in the eighties. Chile and Spain analogy - Aguilar Díaz, Francisco Luis (Revista de Historia Social y de las Mentalidades, 2024)
This paper proposes an approach to the countercultural and new wave phenomena, punk and artistic vanguards of the eighties in Chile, into the context of the military dictatorship, and in Spain, coinciding with the Spanish transition to democracy process and the culture called La Movida Madrileña. The paper will try to define the nature of both models, and understand the evolution in relation to the contexts, from a minority and space to a most influential position in the process of social changes. We also highlight the value of the alternative culture as generator way for experimentation and new ideas, and determining factor in the construction of modern societies.